Necrópolis de incineración y arquitectura funeraria en el noreste de la Península Ibérica durante el Bronce Final y la Primera Edad del Hierro - López Cachero, F. Javier (Complutum, 2008)
In this paper we evaluate the present knowledge on cremation cemeteries from the Late Bronze and Early Iron Age periods in the Northeast of the Iberian Peninsula. We analyze the funerary rites as well as the internal organization of the necropolis paying special attention to the funerary architecture. Our main goal is to characterize the regionalism observed in the territory.
Keywords: Urnfield Culture; Cremation cemetery; Funerary Architecture; Late Bronze Age; Early Iron Age; Northeast of the Iberian Peninsula